Вычислите 1) sin(-n/6)cos(-n/4)- sin(-n/4)cos(-n/6) 2)sin(-n/4)ctg(-n/4)-cos(-n/6)tg(-n/4) 3)sin (-n)+cos(-n/2)tg(-n/4)+ctg(-n/2)

Вычислите 1) sin(-n/6)cos(-n/4)- sin(-n/4)cos(-n/6) 2)sin(-n/4)ctg(-n/4)-cos(-n/6)tg(-n/4) 3)sin (-n)+cos(-n/2)tg(-n/4)+ctg(-n/2)
Гость
Ответ(ы) на вопрос:
Гость
1) sin(-n/6)cos(-n/4)- sin(-n/4)cos(-n/6)=-1/2*√2/2+√2/2*√3/2=√6/4-√2/4=√2/4(√3-1); 2)sin(-n/4)ctg(-n/4)-cos(-n/6)tg(-n/4)=√2/2*1+√3/2*1=√2/2+√3/2=1/2(√2+3); 3)sin (-n)+cos(-n/2)tg(-n/4)+ctg(-n/2)=0-0*1-0=0.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы